The Prosecution of Islamic Criminal Offences Related To LGBT In Online Platforms: An Analysis Of Syariah Criminal Offences (Selangor) Enactment 1995 - Nur Al-Farhain Kamaruzaman; Mashitah Abdul Mutalib; Nur Aina Abdulah; Nurul Ain Hazram (USIM Press, 2024)
Journal of Fatwa Management and Research (JFatwa) Volume 28 No.3 Page (58-70)